The Effectiveness of Using The Blindfold Game to Improve Students' Vocabulary Mastery at SMPN 2 Logas Tanah Darat - Mariyanti, Mariyanti; Eliwarti, Eliwarti; Aruan, Rumiri Rotua (Universitas PGRI Sumatera Barat, 2024)
This pre-experimental research aims to evaluate the efficiency of Blindfold Games in raising SMPN 2 Logas Tanah Darat students' vocabulary mastery. Specifically, the research answers the research questions about how effective is Blindfold Game to improving students’ vocabulary mastery. This study used a one-group pretest-posttest methodology. 30 students from grades 7 were chosen for the sample using cluster random sampling. According to the result, the average the pre-test was 63, while the average for the post-test was 80. For more details, a Paired T-test was conducted on students' pre-test and post-test scores. The results indicate that the Blindfold Game is helps raise students' vocabulary mastery at SMPN 2 Logas Tanah Darat because the Sig. (2 Tailed) the value following the Paired Sample T-test is 0.000, which is smaller than 0.05.